Spatial Spillovers of Conflict in Somalia - Marco Alfano; Thomas Cornelissen (Institute of Labor Economics (IZA), 2022)
Due to economic interconnectedness across regions, locally confined violent conflict may have welfare effects far beyond directly affected areas. This paper focuses on Somalia's al-Shabaab insurgency and investigates whether the food transportation network propagates the effects of violent conflict to distant locations. Combining granular geospatial information on agricultural areas, roads, and itineraries, we show that conflict along transportation routes significantly increases food prices at markets located hundreds of kilometers away. Standardized estimates amount to up to half the magnitude of the effect of rainfall. Negative effects of conflict on road traffic as measured by satellite images of light emissions point towards decreases in food transportation. Moreover, conflict decreases food security, nutrition, health, and education for households living in far-away market areas. This suggests that food prices act as a propagating mechanism that links – among others – human capital to far-away conflict. Back-of-the-envelope calculations suggest that spatial spillovers add an additional 30% to the welfare cost of local conflict.
Keywords: D74; I15; I25; Q18; 330; conflict; spillover effects; food security; health; education